Peran Digital Transformation sebagai Variabel Mediasi antara Visionary Leadership dan Technological Adaptability terhadap Business Readiness (Studi pada UMKM di Kabupaten Grobogan) - Danu Adi Prasetyo; Widiyanto Widiyanto (ARZUSIN, 2026)
This study was motivated by the low level of business readiness among some micro, small, and medium enterprises (MSMEs) in facing an increasingly digital, competitive, and complex business environment. This study aimed to analyze the effect of visionary leadership and technological adaptability on business readiness, both directly and through the mediating role of digital transformation. This study employed a quantitative approach with a survey design. Data were collected through questionnaires administered to MSME actors in Grobogan Regency and were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4.0. The results showed that visionary leadership and technological adaptability had a positive and significant effect on business readiness. In addition, digital transformation was proven to have a positive effect and to mediate the relationship between visionary leadership and technological adaptability and business readiness. These findings confirm that visionary leadership, technological adaptability, and effective implementation of digital transformation are key factors in improving MSME business readiness. The implications of this study emphasize the importance of strengthening leadership capacity, improving technological literacy, and accelerating digital transformation through targeted policy support and training for MSME actors.